1998
DOI: 10.1101/gad.12.24.3857
|View full text |Cite
|
Sign up to set email alerts
|

The RNA cleavage activity of RNA polymerase III is mediated by an essential TFIIS-like subunit and is important for transcription termination

Abstract: Budding yeast RNA polymerase III (Pol III) contains a small, essential subunit, named C11, that is conserved in humans and shows a strong homology to TFIIS. A mutant Pol III, heterocomplemented with Schizosaccharomyces pombe C11, was affected in transcription termination in vivo. A purified form of the enzyme (Pol III ⌬), deprived of C11 subunit, initiated properly but ignored pause sites and was defective in termination. Remarkably, Pol III ⌬ lacked the intrinsic RNA cleavage activity of complete Pol III. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
232
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(249 citation statements)
references
References 80 publications
14
232
2
Order By: Relevance
“…Landrieux et al (2006) showed that C11 RNA cleavage activity is not required for correct recognition of the RNAPIII terminator elements and release of the newly synthesized transcript. However, C11 itself, but not its cleavage activity, is required for reinitiation (Chedin et al 1998;Landrieux et al 2006). These experiments strongly suggest that termination and cleavage of the RNA precursor are not coupled in the RNAPIII transcription process.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 56%
See 1 more Smart Citation
“…Landrieux et al (2006) showed that C11 RNA cleavage activity is not required for correct recognition of the RNAPIII terminator elements and release of the newly synthesized transcript. However, C11 itself, but not its cleavage activity, is required for reinitiation (Chedin et al 1998;Landrieux et al 2006). These experiments strongly suggest that termination and cleavage of the RNA precursor are not coupled in the RNAPIII transcription process.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 56%
“…5). C11 is an essential subunit that mediates the intrinsic RNA cleavage activity of RNAPIII (Whitehall et al 1994) and shows homology with the RNAPII subunit Rpb9 and to RNAPII elongation factor TFIIS (Chedin et al 1998). Landrieux et al (2006) showed that C11 RNA cleavage activity is not required for correct recognition of the RNAPIII terminator elements and release of the newly synthesized transcript.…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 99%
“…Curiously, the homologous subunit in RNA polymerase III, C11, also is essential for the intrinsic cleavage reaction carried out by that polymerase (74). However, there is no TFIIS-like cofactor required to stimulate cleavage for RNA polymerase III.…”
Section: Discussionmentioning
confidence: 99%
“…RNA cleavage leads to a new 3 0 -OH group at the RNA end at the polymerase active site, allowing RNA synthesis to resume [67][68][69]. RNAPs I and III possess a strong intrinsic RNA cleavage activity [70,71 ]. In RNAP III, cleavage activity is so strong that misincorporation cannot be detected unless a cleavagedeficient isoform of the enzyme is used [40 ].…”
Section: Error Removal: Rnap Backtracking and Rna Cleavagementioning
confidence: 99%